Women’s Right to Inheritance in Sharī’ah: Flaws lie in the Society and Judicial System of Pakistan, not in Law on the Subject (A Realistic Jurisprudential Approach) - Attaullah, Qazi; Saqib, Lutf Ullah (Journal of Islamic and Religious Studies, 2020)
Women's right to inheritance, indeed, remains an inconclusive debate almost in all legal systems. Sharī’ah has given extraordinary standing to women's rights. While having an unperceptive study of the work of classical Muslim fuqahā, one can easily derive this fact which is widely accepted by the jurists and legal experts of other legal domains. Moreover, no other prevailing legal system or its jurisprudence can cup-tie Sharī’ah in this connection, both at theoretical and practical levels. Among these rights, the right to inheritance is the most central one. Being an Islamic state, Pakistan follows Sharī’ah for giving up and protecting such rights. However, due to some informal flaws in the society and formal flaws in the judicial system, the implementation of such right becomes frail at ground level, which cannot be a professed failure of Sharī’ah under any stretch of explanation. The present research endeavor outlines, with a solid argument, that the failure lies in the society and prevailing judicial system, of course, not in the law on the subject (i.e. Sharī’ah). The work of the Muslim fuqahā’, both classical and contemporary, has extensively used for certifying this undeniable hypothesis. The historical Islamic jurisprudence, however, is predominantly resorted, herein, for the same purpose. The Pakistani society’s norms and judicial system are profoundly discussed for further clearing-up of the issue. The discourse analysis technique has been followed for the investigation of the issue.